The evolution of religious cognition. (March 2020) - Watts, Fraser
Several accounts of the evolution of religion distinguish two phases: an earlier shamanic stage and a later doctrinal stage. Similarly, several theories of human cognition distinguish two cognitive modes: a phylogenetically older system that is largely intuitive and a later, more distinctively human system that is more rational and articulate. This article suggests that cognition in the earlier stage in the evolution of religion is largely at the level of intuition, whereas the cognition of doctrine or religion is more conceptual and rational. Early religious cognition is more embodied and is more likely to carry healing benefits. The evolutionary origins of religion in humans seem to depend on developments in the cognitive architecture. It is further suggested that the cognition of early religion shows less conceptual differentiation, is characteristically participatory rather than objectifying and is less individualistic. The development of religion in recent centuries appears to show some approximate recapitulation of the stages through which religion originally evolved.